Gender socialization in schools and classrooms - Evans, Hyacinth L.
The findings presented in this paper were gleaned from two research studies that focused on schooling, classrooms, and teaching. Although the study of gender was not the original intent of either study, gender-related observations were made during the data analysis. The data are organized under two headings in the paper: 1) Beliefs and expectations, and 2) Teacher-student interaction
Keywords: Seminar papers